Вплив параметрів АЦП на характеристики радіоприймача на базі DSP. - Білоцерківець, О. Г.; Мальцев, О. С. (ХНУРЕ, 2019)
The introduction of digital signal processing into the radio receiver to improve the reception quality of the signal. The main element in the digital radio is the DSP, but the ADC is equally important. It is from the characteristics of the ADC that depends on the quality of the received signal and its subsequent digitization. The article presents the main characteristics of the ADC and examines in detail the ratio of SNR. The SNR ratios are calculated and a graph of the SNR dependency on IF and ADC discharges is constructed.
Keywords: АЦП; DSP; цифрова обробка сигналів; ЦОС; радіоприймач